(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Teachers of English as a second language in India’s fourth grade were the focus of this study.In this research, eight primary school teachers in the Eastern Cape Province who teach English as asecond language to students in Grade 4 were selected using a random selection technique. We gatheredthis information with the use of a questionnaire with well-considered questions and an observationchecklist, both of which serve as helpful reminders of what to look for. This is why researchers usedboth quantitative and qualitative methods to examine the data. Teachers of English as a SecondLanguage (ESL) in Grade 4 were all conversant with the term teaching strategy, as well as theGrammar Translation Method (GTM), Direct Method (DM), Silent Method (SM), and CommunicativeLanguage Teaching (CLT) approach, but not the Audio-Lingual Method (ALM) or the Total PhysicalResponse (TPR). It’s clear that fourth-grade ESL classrooms only employed one of these two methods,with the GTM serving as a counterpoint to the CLT in most cases.